Strach przed gwałtowną zmianą w społeczeństwie ryzyka = The fear of a sudden change in the risk society - Kampka, Franciszek (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of the article is to re?ect on the social causes and consequences of the fears currently being observed. I present fear as a socially constructed phenomenon, based on individual experiences and supported by media narrations. A risk society is described by Ulrich Beck, Anthony Giddens, Mary Douglas and Michel Foucault as a society experiencing instability and continuous transformation. The conditions of everyday life and the political and economic framework are changing. We are forced to become familiar with new devices and new rules in the labour market. Behaviour standards and criteria for building a social hierarchy are changing. These changes and the fears associated with them are exploited by politicians, which creates the culture of fear described by Frank Furdi and Barry Glassner.
Keywords: społeczeństwo ryzyka; kultura strachu; polityka strachu; zmiana społeczna; society at risk; culture of fear; politics of fear; social change